Prelude to the Anthropocene: Two new North American Land Mammal Ages (NALMAs). (December 2014) - Barnosky, Anthony D; Holmes, Michael; Kirchholtes, Renske; Lindsey, Emily; Maguire, Kaitlin C; Poust, Ashley W; Stegner, M Allison; Sunseri, Jun; Swartz, Brian; Swift, Jillian; Villavicencio, Natalia A; Wogan, Guinevere OU
Human impacts have left and are leaving distinctive imprints in the geological record. Here we show that in North America, the human-caused changes evident in the mammalian fossil record since c. 14, 000 years ago are as pronounced as earlier faunal changes that subdivide Cenozoic epochs into the North American Land Mammal Ages (NALMAs). Accordingly, we define two new North American Land Mammal Ages, the Santarosean and the Saintagustinean, which subdivide Holocene time and complete a biochronologic system that has proven extremely useful in dating terrestrial deposits and in revealing major features of faunal change through the past 66 million years. The new NALMAs highlight human-induced changes to the Earth system, and inform the debate on whether or not defining an Anthropocene epoch is justified, and if so, when it began.